2016
DOI: 10.1371/journal.pone.0166040
|View full text |Cite|
|
Sign up to set email alerts
|

Somite-Derived Retinoic Acid Regulates Zebrafish Hematopoietic Stem Cell Formation

Abstract: Hematopoietic stem cells (HSCs) are multipotent progenitors that generate all vertebrate adult blood lineages. Recent analyses have highlighted the importance of somite-derived signaling factors in regulating HSC specification and emergence from dorsal aorta hemogenic endothelium. However, these factors remain largely uncharacterized. We provide evidence that the vitamin A derivative retinoic acid (RA) functions as an essential regulator of zebrafish HSC formation. Temporal analyses indicate that RA is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 80 publications
1
14
0
Order By: Relevance
“…Presumably, this function is cxcr4 dependent. Indeed another study in zebrafish showed that somite-derived retinoic acid signals induced cxcr4 expression on lateral plate mesodermderived HE during formation of the nascent aorta (Pillay et al, 2016). However, as CXCL12 can interact with other chemokine receptors and integrins (Balabanian et al, 2005;Burns et al, 2006), future studies will be required to determine the precise receptors CXCL12 interacts with to support HSC emergence from aortic HE.…”
Section: The Role Of Chemokines In Hsc Developmentmentioning
confidence: 99%
“…Presumably, this function is cxcr4 dependent. Indeed another study in zebrafish showed that somite-derived retinoic acid signals induced cxcr4 expression on lateral plate mesodermderived HE during formation of the nascent aorta (Pillay et al, 2016). However, as CXCL12 can interact with other chemokine receptors and integrins (Balabanian et al, 2005;Burns et al, 2006), future studies will be required to determine the precise receptors CXCL12 interacts with to support HSC emergence from aortic HE.…”
Section: The Role Of Chemokines In Hsc Developmentmentioning
confidence: 99%
“…RA signaling is required for HSC marker expression even before the formation of the aorta, when the main RA synthesis enzyme, RALDH2, is expressed in the paraxial mesoderm. This requirement is related with the expression of junctional adhesion molecules JAM1a and JAM2a (which are essential for proper transduction of Notch signals), the chemokine CXCL12 and its main receptor CXCR4 [ 50 ].…”
Section: Vitamin A/retinoic Acid In Developmental Hematopoiesismentioning
confidence: 99%
“…Recent work has demonstrated that this juxtaposition is critical for the early events of hemogenic endothelial and HSC specification. Specifically, several groups demonstrated that signals and cells emanating from the somite are required for proper HSC formation within the zebrafish embryo (Clements et al 2011; Kim et al 2014; Kobayashi et al 2014; Lee et al 2014; Nguyen et al 2014; Pillay et al 2016; Pouget et al 2014). …”
Section: 2 Somite-derived Niche Signals Promoting Hsc Productionmentioning
confidence: 99%
“…Important to the hematopoietic field is the discovery that the endotomal cells are not hemogenic endothelial cells, but rather form an endothelial niche that promotes HSC induction from adjacent endothelial cells in a Cxcl12 (CXC chemokine ligand 12)-dependent manner. As a complement to these findings, Pillay et al further characterized somite-derived signaling factors and found that retinoic acid (RA) is required prior to DA formation to regulate components of the Notch and Cxcl12 chemokine signaling pathways (Pillay et al 2016). …”
Section: 2 Somite-derived Niche Signals Promoting Hsc Productionmentioning
confidence: 99%